STUDY OF FLAVONOID CONTENT OF DERMATOCARPON MINIATUM AND LECANORA ARGOPHOLIS LICHENS (Scientific journal of the Fergana State University, 2024)
In the article, for the first time in our Republic, the results of research on the chemical composition of the class of lichens were presented. We all know that flavonoids in plants are important in determining their antioxidant properties. For this reason, in the course of a study using high-performance liquid chromatography (HPLC), the qualitative composition of flavonoids in the lichens Dermatocarpon miniatum and Lecanora argopholis, growing on the territory of our Republic, was studied. Extraction was carried out with 70% ethanol twice at 70-75 0C for 3 h with vigorous stirring and a solvent:plant ratio of 90:20. The solutions were combined by filtration. A 1 mL aliquot was diluted with 9 mL of a solvent system with a 70:30 acetonitrile:buffer (acetate) ratio. It was centrifuged and filtered through a membrane filter. Analysis was performed by HPLC using an isocratic elution mode and a diode array detector (DAD). Acetonitrile and buffer solution were used as mobile phase. Spectral data were studied in the spectral range from 200 to 400 nm.